Strega Nona's gift - DePaola, Tomie, 1934-2020- (Nancy Paulsen Books, 2011)
In Strega Nona's village, the holiday season is a time of celebrations-and nothing says celebration like a feast. All the kitchens are bustling from the Feast of San Nicola, when the children choose the food, to the Feast of Epiphany, when someone gets to be king or queen for the day. Even the animals share in the holiday spirit, and when Big Anthony smells the delicious treats Strega Nona is cooking for them, he decides that just a taste couldn't hurt, right? Wrong. Big Anthony gets his just "desserts," while Strega Nona surprises everyone with a special gift. --From publisher's description.